Effective Enhancement of CO2 Mass Transfer in an Oscillatory Baffled Column: A Comparative Study - Farhan, Omer I.; Mohammed, Harith N.; Ahmed, Safaa M.R. (Journal of Petroleum Research and Studies, 2024)
CO2-water mass transfer was studied in a multi-orifice oscillatory baffled column (OBC) operated in a semi-batch system (batch liquid phase and continuous gas phase). The effect of column configurations, oscillation conditions and gas flow rates, on CO2 concentration ratio (C/Co) in the gas phase, CO2 concentration in water (g/l) and mass flux (g/m2.min) were examined. The experiments were conducted over a wide range of oscillation condition expressed by modified oscillatory Reynolds number ( = 0-1450) and aeration rate, volume of gas per volume of liquid per minute, (vvm = 0-1). The inlet gas stream consists of 15% v/v CO2 (the rest is N2) used to simulate the emission of flue gas streams in industries. The results showed that the mass transfer enhancement increased with oscillation (frequency and amplitude) due to the improved mixing in the OBC. The OBC showed a higher enhancement in CO2-water mass transfer than that obtained with a bubble column (BC) (smooth column without baffles and oscillation), and baffled column (without oscillation). The maximum enhancement of CO2 mass flux achieved in the OBC was 10-fold over the BC at = 1449 and vvm=0.8.